Antibacterial, antibiofilm and cytotoxic properties of prodigiosin produced by a newly isolated Serratia sp. C6LB from a milk collection center. (March 2022) - Jardak, Marwa; Atoissi, Anafy; Msalbi, Dhouha; Atoui, Dhieb; Bouizgarne, Brahim; Rigane, Ghayth; Ben Salem, Ridha; Aifa, Sami; Mnif, Sami
Abstract: The aim of this work was to produce a red tripyrrole pigment prodigiosin from Serratia sp. C6LB strain, to investigate the promising antimicrobial properties on Gram-positive and Gram-negative bacterial strains. The research was also proposed to evaluate the antibiofilm activity on Staphylococcus epidermidis S61 biofilm and its cytotoxic activity against human cancer cell lines. The production and structural elucidation of prodigiosin was carried out using spectrophotometric scanning, TLC, HPLC, FTIR and NMR analysis. The pigment production was optimized using mannose and peptone as carbon and nitrogen sources, respectively. The study confirmed promising antibacterial properties of prodigiosin on eight Gram-positive and Gram-negative bacterial strains with MICs values ranged from 0.039 to 2.5 mg/mL. Antiadhesive activity test of prodigiosin on Staphylococcus epidermidis S61 biofilm exhibited 99.9% inhibition, whereas maximum biofilm eradication activity reached 65%. Cytotoxic activity showed IC50 of 16 μg/mL and 6.7 μg/mL against breast cancer lines MCF-7 and MDA-MB231, respectively. Highlights: Prodigiosin isolation and structural characterization. Optimization of prodigiosin production. Antibacterial and antibiofilm activities of prodigiosin. Cytotoxicity of prodigiosin against cancer cells.